已知多项式A=x²+2y²-z²,B=-4x²+3y²+2z²
2个回答
A+B+C=0
C=-A-B
=-(x²+2y²-z²)-(-4x²+3y²+2z²)
=-x²-2y²+z²+4x²-3y²-2z²
=3x²-5y²-z²
相关问题
已知:x-2y+4z=0,4x-3y+z=0,求2x²+y²+z²/x²+2y²+7z²
已知A=x²+2y²-z,B=-4x²+3y²+2z,且A+B+C=0,则多项式
已知集合a={(x,y,z)|2x y z=4},b={(x,y,z)|3x-y-z=1},C={(x,y,z)|x-2
已知多项式2x^+3y^2+z与多项式7x^2+by^2+3z的差是-x^2+6y^2-2z,求代数式a/b+b/a-a
1.已知多项式A=x^2+2y^2-z^2,B=-4x^2+3y^2+2z^2,且A+B+C=0,则多项式C为( )
已知多项式ax^2+3y^2+z与多项式7x^2+by^2+3z的差是-x^2+6y^2-2z,求代数式a/b+b/a-
2|X-Y|+√2Y+Z+Z²-Z+1/4=0求X+Y+Z的值
已知多项式A=x2+2y2-z2,B=-4x2+3y2+2z2且A+B+C=0,则C为( )
已知多项式A=x2+2y2-z2,B=-4x2+3y2+2z2且A+B+C=0,则C为( )
已知多项式A=x 2 +2y 2 -z 2 ,B=-4x 2 +3y 2 +2z 2 且A+B+C=0,则C为( )